Kapampangan intangible cultural heritage documentation and archiving practices - Martin, Amor C.; Obille, Kathleen Lourdes B.; Rey, Emma M.; Granda, Yolanda C. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2009)
This study looked into the available documentations and archiving practices of cultural repositories or centers in Pampanga. Spiraling and eclectic approaches were the researcher's guiding principles in constructing the design of the study. It involved different methodology for every type of data. It utilized survey-documentary analytical method in identification of available documentations and record Kapampangan Intangible Cultural Heritage (KICH). Face-to-face interview was conducted in collecting information about the archiving practices of target respondents.
The findings revealed that there are 2,497 documented Kapampangan Intangible Cultural Heritage out of 262 consulted sources; and 982 of which are based on original documentations. The domain Oral traditions is the well documented among the five (5) ICH domains and majority of which are Proverbs or Kasabihan. Furthermore, some respondents have unique documentations in terms of the information they contained, and the language used in expressing some KICH. On documents kept in Archives and the archiving practices of respondents, there are no documentations specific to KICH that are stored in archives. Most of the records are still in the active file and are serviced actively among the libraries. These KICH records are kept indefinitely since there are no standard practice observed in selection of items for archiving, which may be probable cause of accumulation of non-archival records. Other non-conformances include: (a) the lack of standard descriptions of inventory and insufficient data supplied, as well the non-use of standard arrangement and description of materials, i. e. General International Standard Archival Description; (d) storing of documentations in work area and exposure to other environmental factors, like foreign matter, dirt, dust, air pollution, exposure to ultra-violet rays etc., which are harmful to the materials.
This research suggests the (a) need to explore and document the least documented KICH domain - Performing Arts and Body Techniques and sub-domains - nursery rhymes; (b) collection of unique sources, like monographs and souvenir magazines in public performances, reenactments, among other KICH, should be considered by libraries and other collecting agencies; (c) formulation of written guidelines in archives and records management will help in appraising and selecting archival materials; the adaption of standard archiving practices will safeguard the archival treasures of the province, like the use of standard format inventory list of General International Archival Descriptions (ISAD-G) will facilitate the retrieval of materials; and application of appropriate preservation techniques like digitization, microfilming, etc., as well as the use of archival materials for preservation, e.g. gold coated optical discs; the transfer of archival sources to separate storage room will protect them from harmful factors; (d) the original materials classified as archival items and are serviced actively should be readily transferred to archives, and access copies should be provided instead to safeguard the materials; and (e) the documentations, including the objects associated with the KICH, should be preserved at the Archives of each cultural agency. Another option is to centrally preserve KICH documentations at the Provincial Archives.
Vita.
Special Problem (Master of Library and Information Science)--University of the Philippines Diliman
Keywords: Archives -- Philippines -- Pampanga; Cultural property -- Philippines -- Pampanga